Gender Equality in the Nordic countries - Faltusová, Kristýna; Hnát, Pavel, 1981-; Smělá, Monika; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
The aim of the thesis is to explore the connection between the concept of Nordic welfare states and gender equality. This will be done by establishing gender equality as a contributor to long-term economic growth, followed by a comprehensive overview of the common attributes of the Nordic model, which will also be put into global comparison. Moreover, the thesis will also contribute to the ongoing conversation about gender equality in the Nordic countries by providing a thorough examination of the current state of family policies in the Nordics. Lastly, in spite of the Nordic model, the thesis seeks to pinpoint possible discrepancies and deviations among the countries. Data from online databases from organisations such as OECD, Worldbank, the Nordic Statistics and Eurostat will be used.
Vedoucí práce: Pavel Hnát
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses